FACTORS CORRELATED TO LEAMING ACHIEVEMENT OF THE STUDENTS OF STATE SENIOR HIGH SCHOOL 14 OF MAKASSAR - Edward Claproth (Stikes Graha Edukasi Makassar, 2019)
Introduction :Learning achievement is the result of leaning activity process which causes a change of students' behavior. Such a change involves knowledge, skill, and attitude aspects. Those aspects are then evaluated and actualized in numbers and scores as seen in their report book. The aim of the rese correlated to learning achievement of the students of State Senior High School 14 of Makassar. Method: This research was a cross sectional design. The populations were male students of Class XI of State Senior High School 14 of Makassar consisting of 77 students. The sample was selected using proportional stratified random sampling technique. The data were obtained through questionnaire and observation sheets. Result: The results of the chi-square test indicate that there is a significant value of p = 0.004 meaning that there is a significant correlation between smoking behavior and students' learning achievement. The result of kolmogrov-smirnov test indicates the value of p = 0.000 meaning that there is a significant correlation between parents' economic status and students' learning achievement. The result of chi-square test indicates the value of p = 0.983 meaning that there is insignificant correlation between class program and students' learning achievement. Conclusion : There is correlation among smoking behavior, parents’ economic and class program with student’s learning achievement.